2022
DOI: 10.3390/electronics11020196
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Operation of a Microgrid with Hydrogen Storage Based on Deep Reinforcement Learning

Abstract: Microgrid with hydrogen storage is an effective way to integrate renewable energy and reduce carbon emissions. This paper proposes an optimal operation method for a microgrid with hydrogen storage. The electrolyzer efficiency characteristic model is established based on the linear interpolation method. The optimal operation model of microgrid is incorporated with the electrolyzer efficiency characteristic model. The sequential decision-making problem of the optimal operation of microgrid is solved by a deep de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Recent studies on the optimised control of SENs having multiple ESSs like a hybrid of a BESS and a HESS are proposed in [8,[30][31][32][33]. In [8,30], a DDPG-based algorithm is proposed to minimise building carbon emissions in an SEN that includes a BESS, an HESS, and constant building loads.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on the optimised control of SENs having multiple ESSs like a hybrid of a BESS and a HESS are proposed in [8,[30][31][32][33]. In [8,30], a DDPG-based algorithm is proposed to minimise building carbon emissions in an SEN that includes a BESS, an HESS, and constant building loads.…”
Section: Related Workmentioning
confidence: 99%
“…In [8,30], a DDPG-based algorithm is proposed to minimise building carbon emissions in an SEN that includes a BESS, an HESS, and constant building loads. Similarly, operating costs are minimised in [31] using DDPG and in [32] using DQN. However, these studies use a single control agent to manage the multiple ESSs.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, in ref. [23], the authors develop a deep deterministic policy gradient algorithm to reduce the operating costs of a microgrid with hydrogen storage by simulation, compared to traditional algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it can also be found that green hydrogen could be economically competitive with hydrogen produced from steam-methane reformation [14] or a quick and significant reduction in the costs of Li-ion batteries [15]. To make RESs and storage systems economically competitive for self-consumption, there are different proposals that can be classified between the following: (1) Those focused on the energy-management strategy (EMS), such as a mixed-integer linear-programming (MILP) model to minimise the operating cost of a microgrid [16], or the use of a deep deterministic policy-gradient algorithm in order to reduce microgrid operating costs [17]. (2) Those based on the use of low-cost materials and equipment for the microgrid, such as the use of a photoluminescent (PL) absorber of luminescent solar power (LSP) to reduce solar-PV energy costs [18], or the use, in redox flow batteries (RFBs), of low-cost polymeric redox-active materials and porous size-exclusion membranes of commodity polymers instead of more expensive options like inorganic redox-active materials and ion-exchange membranes, respectively [19].…”
Section: Introductionmentioning
confidence: 99%